Comparative Analysis of Energy Performance of Building Energy Efficiency Rating and Zero Energy Certified Buildings for Neighborhood Facilities - Seo, Jae Sang; Kim, Sun Sook (Journal of the Architectural Institute of Korea, 2023)
The drive for Zero Energy Building Certification (ZEB) is gaining momentum to boost the energy efficiency of new buildings and work towards a carbon-free future by 2050. As of 2023, public buildings with over 500 square meters of floor space are required to attain ZEB Certification, and this requirement will extend to private buildings in 2025. Since neighborhood facilities make up a significant portion of these new buildings, the impact of this extension will be substantial. To prepare for the mandatory ZEB Certification for private buildings, this study conducted a comparative analysis of the Building Energy Efficiency Rating (BEER) System and ZEB Certification for neighborhood facilities. The energy performance and essential technologies for these structures were also analyzed.
Keywords: Building Energy Efficiency Rating System (BEER); Energy Performance; Neighborhood Facility; Zero Energy Building (ZEB)